The Implementation of A No Smoking Area Policy at The Tomohon’s DPRD Secretariat Office - Itje Pangkey; Fitri Mamonto; Monika Alfa Paat (Syntax Corporation Indonesia, 2022)
This research aims to describe the implementation and the aspects that hinder the No Smoking Area Policy at the Tomohon’s DPRD Secretariat Office. This research uses descriptive qualitative method. The data in this study were obtained from interviews and documentation. The informants in this study were the Head of the Trial and Legislation Section, the Head of the Trial, Minutes and Publications Sub-Section, the Head of the Equipment and Household Sub-Division, as well as the staff of the Tomohon’s DPRD Secretariat Office. The results of the study show that the implementation of the No Smoking Area policy at the Tomohon’s DPRD Secretariat Office has not been fully implemented properly. The socialization has been carried out since the implementation of the No Smoking Area policy. The readiness for implementation has not fully demonstrated an attitude that supports the No Smoking Area policy at the Tomohon City DPRD Secretariat Office. There are still employees who do smoking activities not in the space provided. The office head has not implemented strict sanctions related to the Non-Smoking Area.